Near-Infrared Bioluminescence Imaging of Macrophage Sensors for Cancer Detection In Vivo - Zambito, Giorgia; Mishra, Gunja; Schliehe, Christopher; Mezzanotte, Laura (Frontiers in Bioengineering and Biotechnology, 2022)
Melanoma is an aggressive type of skin cancer with a poor prognosis after it metastasizes. And the early detection of malignant melanoma is critical for effective therapy. Because melanoma often resembles moles routine skin check-ups may help for timely identification of suspicious areas. . Recently, it has been shown that the interplay of melanoma cells with the immune system can help to develop efficient therapeutic strategies. Here, we leverage engineered macrophages (BMC2) as cell-based sensors for metastatic melanoma. To perform a dual-color bioluminescence imaging (BLI) in vivo, macrophages were engineered to express a green click beetle luciferase (CBG2) and a near-infrared fluorescent dye (DiR), and B16F10 melanoma cells were instead engineered to express a near-infrared click beetle luciferase (CBR2). Using a real-time in vivo dual-color BLI and near-infrared fluorescence (FL) imaging, we could demonstrate that macrophages were able to sense and substantially accumulate in subcutaneous and metastatic melanoma tissues at 72h after systemic injections. Together, we show the potentiality to use optical imaging technologies to track circulating macrophages for the non-invasive detection of metastatic melanoma.